SOME PRINCIPLES IN THE FORMATION OF ORGANIC MATTER DURING THE EARLY STAGES OF CHEMICAL EVOLUTION - Gribov L.A. (My University, 2007)
The origin of the diversity of organic compounds on the Earth, up to the development of processes that determine the possibility of life itself, is one of the most interesting problems in cognition of the world. It is generally recognized that all vital processes proceed, so to say, in the world of molecules, which were, in turn, formed by the gradual complication of constituents of this world (molecular structures), beginning from protozoa. It is hardly possible to trace in detail the entire evolution of the conditions leading to the formation of vitally important processes in the molecular world, but some of the most important concepts can hopefully be perceived based on the ab-initio principles, i.e., under the assumption that all processes are rooted in the fundamental natural laws, primarily, those formulated in physics.